Chronic IVC occlusion caused by unopened filter after conversion: case report and literature review - Shi Sheng; Yiqing Li (Frontiers in Cardiovascular Medicine)
BackgroundThe VenaTech Convertible Vena Cava Filter (VTCF) is a device designed for insertion into the inferior vena cava (IVC) to prevent life-threatening pulmonary embolism (PE). Upon removal of its retrieval hook, the filter's legs are intended to expand, forming a stent-like structure that is suitable for long-term residence in the human body. However, in clinical practice, the filtering legs do not always expand fully, and the long-term effects on patients remain insufficiently studied.Materials and methodsThis report presents the case of a male patient with thrombophilia, in whom the VTCF failed to expand completely after conversion, resulting in IVC occlusion and the development of acute deep vein thrombosis (DVT) in the lower limbs. A review of the relevant literature is also provided.ConclusionThe inability of the filtering legs to fully expand after retrieval hook removal highlights a design limitation of the VTCF, necessitating proactive management during conversion to ensure complete expansion. For younger or thrombophilic patients, careful evaluation of the filter's suitability and extended follow-up are crucial to optimize outcomes.